Removal efficiency of multiple poly- and perfluoroalkyl substances (PFASs) in drinking water using granular activated carbon (GAC) and anion exchange (AE) column tests. (1st September 2017) - McCleaf, Philip; Englund, Sophie; Östlund, Anna; Lindegren, Klara; Wiberg, Karin; Ahrens, Lutz
Abstract: Poly- and perfluoroalkyl substances (PFASs) have been detected in drinking water at relatively high concentrations throughout the world which has led to implementation of regulatory guidelines for specific PFASs in drinking water in several European countries and in the U.S. The Swedish National Food Agency has determined that the drinking water of over one third of the country's municipal consumers is at risk or already affected by PFAS contamination. The present study investigated the effects of perfluorocarbon chain length, functional group and isomer structure (branched or linear) on removal of multiple PFASs using granular activated carbon (GAC, Filtrasorb ® 400) and anion exchange (AE, Purolite ® A600) column experiments. The removal of 14 different PFASs, i.e. the C3 C11, C14 perfluoroalkyl carboxylic acids (PFCAs) (PFBA, PFPeA, PFHxA, PFHpA, PFOA, PFNA, PFDA, PFUnDA, PFDoDA, PFTeDA), perfluorooctane sulfonamide (FOSA), and the C4, C6, C8 perfluoroalkyl sulfonic acids (PFSAs) (PFBS, PFHxS, PFOS), was monitored for a 217 day period. The results indicate the selective nature of PFAS removal as the absorbents are loaded with PFASs and dissolved organic carbon (DOC). A clear relationship between perfluorocarbon chain length and removal efficiency of PFASs using GAC and AE was found while PFASs with sulfonate functional groups displayed greater removal efficiency than those with carboxylate groups. Similarly, time to column breakthrough increased with increasing perfluorocarbon chain length and was greater for the PFSAs than the PFCAs for both GAC and AE. Shorter carbon chained PFASs such as PFBA, PFPeA, PFHxA showed desorption behavior and long-chained PFASs showed increased removal towards the end of the experiment indicating agglomeration or micelle development. Linear isomers of PFOS, PFHxS, and perfluorooctane sulfonamide (FOSA) had greater column removal efficiencies using GAC (and also for AE at greater bed volume throughput) than the branched and this difference increased at greater bed volume throughputs. The GAC and AE columns showed a poor correlation between DOC and PFAS removal efficiency. The results indicate that designers and operators of AE and GAC treatment processes must take into consideration the selective nature of PFAS removal and associated desorption of short-chain PFCAs during co-removal of multiple PFASs. Graphical abstract: Highlights: Multiple PFASs were successfully removed using GAC and AE columns. Average removal efficiencies and time to breakthrough decreased in the following order PFSAs ≈ FOSA > PFCAs. Short-chained PFASs showed de-adsorption and long-chained PFASs agglomeration. Linear PFAS isomers had greater removal efficiencies than branched ones using GAC. Lin&Huang adsorption model is suitable to predict the PFAS removal for GAC and AE.